MANUSCRIPT OF KARANG MINDU KERINCI (LAMENTATION LITERATURE WITH INCUNG SCRIPT) - Syaputra ZE, Deki (Walasuji : Jurnal Sejarah dan Budaya, 2020)
Incung letter is one of the scripts used in writing scripts or manuscripts in Kerinci by using various media, one of them is bamboo. The use of bamboo in the tradition of writing in Kerinci is only for texts using incung script. The manuscripts made from bamboo and using incung include mostly literary works in the form of lamentations (karang mindu) that use Kerinci Malay language which is very difficult to understand and very rarely used because few speakers who knows it anymore. Therefore, the author in this paper presents transliteration and translation of several lamentation texts as well as the contents and related meanings. In this paper, the texts with incung script that will be discussed is Wailing Tears Manuscripts collected by Bachtiar Anif Siulak and Manuscript of TK 182 which are analyzed through descriptive analytical methods and philological and codicological approaches. From this research, it can be known that the content of Wailing Tears Manuscript consists of two things, namely the fate of one's life and love lamentations. Both of these manuscripts are written directly by the person who is lamenting and some are written by others at the request of the weeping.